2011
DOI: 10.1177/0145721711411312
|View full text |Cite
|
Sign up to set email alerts
|

Family Inclusion in Diabetes Education: A Nationwide Survey of Diabetes Educators

Abstract: Diabetes educators without formal exposure to family theory may be overestimating how much they emphasize family support in diabetes education. Increasing formal education about the importance of family involvement in self-management behaviors could positively affect individual diabetes self-management outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 27 publications
0
34
0
Order By: Relevance
“…Given the high prevalence of T2DM among Hispanics and the value placed on the family, nurses including diabetes educators and other health care providers need to emphasize family self-efficacy for diabetes management to positively affect diabetes outcomes (Denham et al, 2011). Future testing of the FSE with this population is needed to elucidate the influence of family self-efficacy on behavior changes for successful diabetes management.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the high prevalence of T2DM among Hispanics and the value placed on the family, nurses including diabetes educators and other health care providers need to emphasize family self-efficacy for diabetes management to positively affect diabetes outcomes (Denham et al, 2011). Future testing of the FSE with this population is needed to elucidate the influence of family self-efficacy on behavior changes for successful diabetes management.…”
Section: Resultsmentioning
confidence: 99%
“…The Hispanic family and familism values exert critical influence on health status, decision making about individual health care, and the procurement of health services made by the family (Perez & Cruess, 2014; Wen et al, 2004). A growing body of research elucidates the necessity of considering family values and the integration of family into treatment regimens (Perez & Cruess, 2014) and design of diabetes educational interventions (Denham, Ware, Raffle, & Leach, 2011; Hu et al, 2014; Wen et al, 2004). Building family self-efficacy for T2DM management can yield significant behavior change in the family environment that influences T2DM disease management.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple approaches to family interventions as to improve diabetes self-management have been examined [13]. However, theoretical knowledge about family theory and family-based education seem to be lacking among diabetes educators influencing the impact of the intervention [14]. …”
Section: Introductionmentioning
confidence: 99%
“…14 Research has shown the behavioral influence of family members on diabetes self-management of patients with diabetes 15 (Chesla, Fisher, 2003). Thus, including family members in the diabetes education programs may improve patients’ adherence to diabetes self-management regimens 16 (Denham, Ware, Raffle & Leach, 2011). Providing accurate information on diabetes and risk factors associated with diabetes to family members may enhance family support and develop healthy behaviors for the entire family Denham, 2003; 16,17 Denham, Ware, Raffle & Leach, 2011).…”
mentioning
confidence: 99%